Effect of allithiamine on the level of hyperglycaemia-induced advanced glycation end products - Bíró, Attila; Remenyik, Judit (Acta Agraria Debreceniensis, 2019)
Diabetes mellitus is a rapidly growing public health burden in both developed and developing countries. Diabetes mellitus is accompanied by hyperglycaemia, which can cause tissue injury by several mechanisms. One of these is the formation of advanced glycation end-products (AGEs). In this study, the effect of allithaimine, a fat-soluble thiamine derivative, was investigated on hyperglycaemia-induced AGEs levels using human umbilical cord vein endothelial cells (HUVECs) as a hyperglycaemic model. HUVECs were isolated by enzymatic digestion, characterized by flow cytometer and treated 30 mM glucose plus allithaimine or thiamine or cell maintenance medium as control.  Allithiamine was synthesized and purified. The structure of the synthesized and isolated compound was verified by reverse phase HPLC and MALDI-TOF. AGEs were evaluated by ELISA. Collectively, our results indicate that allithiamine can reduce level of the hyperglycaemia-induced AGEs similar to thiamine.